Longitudinal Changes in Religiosity in Dutch Society and Drama Programs on Television, 1980-2005 - Emons, Pascale (Journal of media and religion, 2009)
In this study, we examined the relationship between changes regarding religious practices and beliefs in Dutch society as ascertained in longitudinal surveys and indicators of these social cultural trends as witnessed in drama programs on Dutch television. A sample of 503 prime-time programs aired between 1980 and 2005, with a total number of 2,114 identified main characters, was selected for systematic content analysis. The findings showed a marked decrease in the proportion of main characters with an identifiable religious orientation and the number of programs with religious minor characters over this period of time. The occurrence of religious themes in storylines in programs also had decreased. Institutional religion plays a rapidly decreasing role in Dutch society and religious content in Dutch drama television is all but absent. Our main conclusion is that longitudinal changes in the representation of religion in Dutch television drama seem to precede changes in the role and perception of religion in Dutch society.